Work demand and voluntary turnover intention of independent auditors - Weissmantel, Cristiane Wornath (2024)
This study aimed to analyze the influence of work demand on the voluntary turnover intention of independent auditors, considering the mediating effects of work engagement and Burnout Syndrome. The research is descriptive, of the survey type, with a quantitative approach, and includes a sample of 196 Brazilian independent auditors. The results confirmed the positive association between work demand and the voluntary turnover intention of auditors. Additionally, it was evidenced that work engagement acts as a mediator in this relationship. On the other hand, Burnout Syndrome does not play a mediating role in the relationship between work demand and turnover intention. Finally, it was observed that work engagement exerts a negative and neutralizing influence on Burnout Syndrome. These findings provide auditing firms with a deeper understanding of the antecedents of independent auditors' turnover intention.